Multiliteracies and the portuguese language curriculum component: a case study of technical education in the state of São Paulo - Bachur, Maria Fernanda Merlino Domenes; Oliveira , Sheila Fernandes Pimenta e; Bandos, Melissa Franchini Cavalcanti (The ESPecialist, 2024)
The Pedagogy of Multiliteracies can be introduced to foster a continuously evolving and reconstructing knowledge base, aimed at critical development through the integration of theory, practice, and the student's reality within the school context. This understanding can promote social development and a pursuit of freedom beyond economics, that is, a consciousness as an active citizen (Freire, 1967) included in societal transformations (Sen, 2000). Novotec is a professional high school education program and is currently offered as a training pathway within the New High School structure. Thus, this study seeks to address the following research question: what are the effects of a Pedagogy of Multiliteracies in the Portuguese language on the formation of students in the Novotec technical program, enabling social development? In this sense, the main objective is to reflect on knowledge construction in Portuguese language education within the technical training provided by Novotec through the Pedagogy of Multiliteracies, with the aim of observing potential impacts on social development, especially in education. The methodology includes historical and bibliographic discussions, as we aim to correlate social development in the educational and technological spheres for individual transformation and autonomy. Therefore, to build the research corpus, considering the categories of multiliteracies in the design context, an action research (Thiollent, 1986) was conducted with high school students enrolled in the Novotec program, based on a project developed in the second year of high school that emphasized the use of technology and various languages in multimodal contexts. The resulting projects constituted the research data, which were analyzed and compared with the general competencies outlined in the BNCC (Brazilian National Common Curricular Base). The results demonstrated the students' command of knowledge objects, the skills associated with study and research fields, as well as journalistic-media fields, particularly with regard to the documentary genre, including proficiency in audiovisual techniques and technologies. Certainly, a formation geared towards citizenship and future employment.